Cytogenetic Studies of Individuals from Four Kindreds with Multiple Endocrine Neoplasia Type II Syndrome - Butler, Merlin G. (Cancer Genet Cytogenet, 1987)
Multiple endocrine neoplasia type II (MEN-II) syndrome is an autosomal dominant condition characterized by medullary carcinoma of the thyroid, pheochromocytoma, and parathyroid adenoma. A cytogenetic investigation was conducted on 13 MEN-II syndrome patients from four unrelated kindreds and 13 age-matched control subjects for chromosome instability and the chromosome 20 deletion reported in MEN-II syndrome. A significant increase (p < 0.05) was found in the total number of chromatid and chromosome aberrations in MEN-II cells (12.3%) compared with control cells (6.9%) grown at 96 hours in mitomycin C (20 ng/ml, final concentration). The major difference between the two groups was in chromatid, and not chromosome, aberrations. There was no difference between MEN-II and control individuals in fragile site expression, the number of sister chromatid exchanges or cell kinetics. A blind analysis of high-resolution G-banded chromosomes was performed on blood specimens from 13 MEN-II and seven control individuals. Twelve of 13 MEN-II patients and one of seven control subjects were scored as having a 20p12.2 deletion (χ(2) = 12.6; p< 0.001). Additional research is needed to determine if this cytogenetic finding is due to a chromosome deletion, inversion, or polymorphism.